The Derivatives Market in South Africa : Lessons for Sub-Saharan African Countries - Adelegan, Olatundun Janet (IMF Working Papers; Working Paper ;, 2009)
This paper examines the role of the derivatives market in South Africa and provides policy options for promoting the development of derivatives markets in sub-Saharan Africa. South Africa's derivatives market has grown rapidly in recent years, supporting capital inflows and helping market participants to price, unbundle and transfer risk. There are tight regulations on asset allocations by insurance and pension funds to prevent excessive risk taking. The development of derivatives markets in sub-Saharan African countries could enable market participants to self-insure against volatile capital flows. Theiroverdependence on bank credit as a source of funding could be reduced and their management of seasonal risk could be improved through the introduction of commodity futures. However, these markets must be appropriately regulated and supervised. Since such markets would likely be small, consideration should be given to the establishment of a regional derivatives market.